Kinetics and wear behaviour of M50NiL steel plasma nitrided at low temperature - Yan, M. F.; Wang, X. A.; Liu, R. L.; Zhang, Y. X.; Yang, Y. (Materials science and technology, 2017)
The quenched M50NiL steel was plasma nitrided at 460°C for different time to investigate the effects of the duration time on the microstructure, microhardness and wear resistance of the nitrided layers. The results show that the plasma nitrided layer depth increases with increasing nitriding time. The plasma nitrided layer includes only the diffusion layer without compound layer. The main phases in the nitrided surface layer are nitrogen expended α′-Fe and γ′-Fe 4 N. The microstructure of the nitrided layer is refined. The wear resistance of the nitrided samples can be improved significantly by plasma nitriding. The sample nitrided for 4 h possesses the highest wear resistance, due to its relatively smooth surface and ultra-fine grains in the nitrided layer.